PENGUATAN MANAJEMAN UMKM BERBASIS MOBILE PADA USAHA KEBAB - Berliana Siregar; Diajeng Mulyani; Parameswari, Nazma (Jurnal Manajemen dan Pemasaran, 2025)
ABSTRACT enhancement of Micro, Small, and Medium Enterprises (MSMEs) management through technology-based assistance for the "Kebab You" business. The primary focus of this initiative is to provide a mobile application-based information system to improve the efficiency of financial transaction recording and business analysis. Observations identified that the partner faced difficulties due to the absence of a structured accounting system, hindering business decision-making and performance evaluation. The developed application, BukuWarung, is designed to facilitate financial record-keeping, stock management, expenditure tracking, and the preparation of simple yet accurate profit and loss reports. The implementation results show that this application assists the partner in understanding their financial position and determining effective marketing strategies. Moreover, this initiative aims to contribute to MSME development by leveraging digital technology in business management